2014
DOI: 10.1096/fj.13-247759
|View full text |Cite
|
Sign up to set email alerts
|

EphB2 contributes to human naive B‐cell activation and is regulated by miR‐185

Abstract: EphB2 is an important member of the receptor tyrosine kinases. Recently, EphB2 was shown to facilitate T-cell migration and monocyte activation. However, the effects of EphB2 on B cells remain unknown. In this study, the expression of EphB2 on B cells was tested by Western blot, and the roles of EphB2 in B-cell proliferation, cytokine secretion, and immunoglobulin (Ig) production were evaluated using EphB2 siRNA interference in human B cells from healthy volunteers. Our study revealed that EphB2 was distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Some number of miRNA have been reported to modulate immune processes. Mir-26a-5p, mir-140-3p and mir-339-5p, for example, can inhibit NF-κB expression [4244]; and mir-185-5p and mir-200a-3p can regulate immune cell proliferation and differentiation [45, 46]. While to role of miRNAs has largely been studies in cells, miRNAs can also readily be found in the blood.…”
Section: Regulation Of Stress-induced Sterile Inflammation: Mirna Andmentioning
confidence: 99%
“…Some number of miRNA have been reported to modulate immune processes. Mir-26a-5p, mir-140-3p and mir-339-5p, for example, can inhibit NF-κB expression [4244]; and mir-185-5p and mir-200a-3p can regulate immune cell proliferation and differentiation [45, 46]. While to role of miRNAs has largely been studies in cells, miRNAs can also readily be found in the blood.…”
Section: Regulation Of Stress-induced Sterile Inflammation: Mirna Andmentioning
confidence: 99%
“…The regulation of apoptosis during Gc B cells maturation is tightly regulated, the anti-apoptotic bcl-2 protein is down-regulated in Gc B cells and both Gc elevated mir-15a and mir-16 directly inhibit it 136 . mature B cells express mir-150 and mir-185, but expression of both is after activation reduced 131,137 . The mir-185 indirectly supports B cell activation such as production of igG and TNF-α cytokine while negatively regulate the ephB2 expression 137 .…”
mentioning
confidence: 99%
“…mature B cells express mir-150 and mir-185, but expression of both is after activation reduced 131,137 . The mir-185 indirectly supports B cell activation such as production of igG and TNF-α cytokine while negatively regulate the ephB2 expression 137 . on contrary, mir-210 is induced after B cell activation 130 .…”
mentioning
confidence: 99%
“…A very interesting observation is related to miR-185 expression pattern: published results, in fact, demonstrated that this miRNA was upregulated in mouse GC B cells and downregulated in human GC B cells after stimulation of naïve B cells with lipopolysaccharide antigen [21, 35]. MiR-185 is able to switch off the BTK kinase, that plays a critical role in controlling the positive and negative selection of autoreactive B cells in mice [36], by influencing the B cell receptor signaling pathway [21].…”
Section: Discussionmentioning
confidence: 99%